How to speak dragonese (book 3)/. - Cowell, Criselda (New York : Little Brown and Company, 2005)
Recounts the further escapades of Hiccup Horrendous Haddock the Third as he continues his Viking training during which he escapes from a boatload of Roman soldiers and searches for his kidnapped dragon.
Keywords: Vikings- -- juvenile fiction; Dragons- -- fiction; Vikings- -- fiction; Humorous stories